TINJAUAN ASPEK FISIK DAN NON FISIK SISTEM DRAINASE ZONA 5 KOTA BANDA ACEH - Ari Herfiansyah; Eldiana Fatimah; Azmeri Azmeri (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Based on the results of the Environmental Health Risk Assessment Study, zone 5 of the drainage in Banda Aceh City which includes Syiah Kuala, Ulee Kareng, and Kuta Alam Sub-district, some villages fall into the category of moderate-risk and high risk of inundation. Bandar Baru, Lambaro Skep, Ie Masen Kayee Adang, and Lambhuk are moderate risk villages of inundation. This study aims to evaluate the performance of the drainage system to see how the conditions and functions of the drainage facilities and infrastructure that have been built and the participation of the society. The methodology used in this study is quantitatively supported by descriptive-evaluative. Performance reviews conducted include physical and non-physical aspects. Physical aspects include physical data on infrastructure, the function of drainage system infrastructure, and operating and maintenance conditions for drainage. Non-physical aspects include regulations/institutions, development management, and efforts by the Regional Government to encourage society/private participation. The results of the calculation of drainage performance obtained a value of 81.40 which means the performance is in good condition. Physical aspects value 55.0 and non-physical aspects value 26.4. From the physical aspect of the condition of drainage infrastructure such as drainage canals, pump houses, retention ponds are already in good condition, but some sluice gates are still in a damaged condition that has not been repaired. From the non-physical aspects, some of the shortcomings that must be corrected are the absence of regional regulations for drainage, human resources in agencies that handle drainage are still not optimal, and community participation in managing drainage is still minimal.